PERTANGGUNGJAWABAN PIDANA ATAS PEMBERITAAN YANG TERINDIKASI ADANYA PENCEMARAN NAMA BAIK DIKAITKAN DENGAN HAK JAWAB DALAM UNDANG-UNDANG NOMOR 40 YAHUN 1999 TENTANG PERS (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Criminal liability for reporting indicated by the existence of defamation associated with the right of reply in Act No. 1999 concerning the Press is a provision that must be carried out by the public or the press relating to a news. The existence of defamation cases has developed in accordance with the era not only through newspapers but also through the internet. The press is a lex specialis (more specific law) on the provisions of criminal law (KUHP) so that in this case the provisions used are the Press Law, things that are not regulated in the press will refer to the provisions in the Criminal Code. In fact, there are still press who are held accountable based on the provisions of criminal law relating to the right of reply in Article 5 paragraph (2) and in some decisions the journalists are prosecuted for these provisions. The purpose of this thesis is, firstly: To find out the criminal liability for reporting which is indicated by the existence of defamation associated with the right of reply in law number 40 of 1999 concerning the press. second: To find out the right of reply as referred to in Article 1 number 11, law number 40 of 1999 can give consideration to the judge in giving a decision on the news which indicates a defamation.This type of research is normative juridical research, namely research conducted by examining the literature discussion with secondary data sources consisting of primary legal material in the form of legislation, legal material and tertiary legal discussion in the form of a dictionary. Then the data is analyzed qualitatively, namely analyzing data descriptively obtained from secondary data.From the results of the study it can be concluded that, first, criminal liability for defamation is carried out by the press. then the person who must be accounted for in the trial is the editor in chief or the editorial field whose provisions are contained in Article 12 and based on Articles 55 and 56 of the Criminal Code. Secondly, the provisions of the right of answer stipulated in Article 5 paragraph (2), where when a press defames a person's name in a news, the press must serve the right of reply. Even though the right of answer has been carried out by the press and ethically the problem has actually been considered complete, it does not rule out the possibility that the party who feels disadvantaged continues the matter to the court, remembering the Press Law does not prohibit this.Keywords : Criminal Accountability - News - Defamation - Rights Reply.